A implementação do IFRS 15 no Brasil: análise das mudanças nos processos e controles internos para reconhecimento da receita nos contratos de construção - Tavares, Thiago Napolitano (2016)
The issuance of IFRS 15 is significant a change in the process of convergence of accounting practices adopted by FASB and IASB. The implementation of an almost uniform standard that controls the revenue recognition will bring important changes in the environment of internal controls and processes of the companies. Though the adoption of IFRS 15 is effective from January 1, 2018, it’s necessary to prepare an advance mapping in order to measure the scale of the changes and implement them in the context of each organization considering the sector of activity and types of contracts. This research specifically addresses the impacts identified in the construction contracts. This research has qualitative and exploratory characteristics because there are no studies that already identified the impacts by applying the new standard. The final result of this research has been obtained through interviews with auditors and accountants specialized in construction contracts, especially considering the importance of knowing the impact perceived by those who prepare the financial statements and by whom audits itself. Important changes have been identified, particularly in the revenue recognition process, as the new standard requires greater analysis on contractual clauses and essence of contracts under the accounting perspective. Among the findings are: change in the number of performance obligations, estimates of variable consideration for revenue recognition and identification of financial component on the contracts. Accountants and auditors of companies with construction contracts are the main users of the impacts identified in this research.